Adverse effects of polymyxin B administration to healthy horses. (7th July 2022) - van Spijk, Julia N.; Beckmann, Katrin; Wehrli Eser, Meret; Boxler, Martina; Stirn, Martina; Rhyner, Thea; Kaelin, Dana; Saleh, Lanja; Schoster, Angelika
Abstract: Background: Polymyxin B (PolyB) is used to treat endotoxemia in horses; neurologic and nephrogenic adverse effects occur in humans. Objectives: To describe PolyB adverse effects in horses. Animals: Five healthy horses (ataxia 0/5), 1 horse with cervical osteoarthritis (ataxia 1/5). Methods: Prospective blinded randomized cross‐over trial; 3‐weeks wash out. Horses received PolyB (PolyB 6000 IU/kg IV, 7 doses q12h, n = 6) and PolyB/gentamicin (PolyB 6000 IU/kg IV, q12h 7 doses; gentamicin 10 mg/kg IV q24h 4 doses n = 4, or q12‐24 h 5 doses because of an additional erroneous dose, n = 2). Daily neurological examinations were video recorded, and ataxia graded by 3 observers. Urine status, urinary GGT/creatinine ratio, plasma creatinine, and urea were assessed every other day, EMG daily. Mixed model analysis was used to evaluate factors associated with ataxia grade and [PolyB]. Results: Median ataxia score increased from 0/5 (range 0‐2/5) to 2/5 (range 1‐3/5) during administration and declined to 0.5/5 (range 0‐2/5) after cessation. Gentamicin co‐administration ( P < .01, effect size: .8), number of PolyB doses ( P < .001, effect size: .6), and time since last PolyB dose ( P < .001, effect size: .5) had a significant effect on ataxia grades, while horse, day, [Genta], [PolyB], and [PolyB]CSF did not. Gentamicin co‐administration and [Genta] Cpeak had no effect on median [PolyB] Cpeak (4.67 and 4.89 μg/ml for PolyB and PolyB/gentamicin, respectively). Urinary GGT/creatinine ratio was elevated in 3/6 horses receiving PolyB/gentamicin. The EMG remained unchanged. Conclusions and Clinical Importance: PolyB caused transient ataxia, worsening with cumulative PolyB doses and gentamicin co‐administration. Nephrotoxicity of PolyB was only evident when gentamicin was co‐administered.